Conservative orators : From Baldwin to Cameron - Crines, Andrew Scott; Hayton, Richard (Book collections on Project MUSE., 2016)
How do Conservative politicians strive to communicate with and influence the electorate? Why have some proven more effective than others in advancing their positions and ideological agendas? How do they seek to connect with their audience in different settings? This book draws analytical inspiration from the Aristotelian modes of persuasion to shine new light upon the articulation of British conservatism, examining the oratory and rhetoric of twelve key figures from Conservative Party politics. The individuals featured are Stanley Baldwin, Winston Churchill, Harold Macmillan, Iain Macleod, Enoch Powell, Keith Joseph, Margaret Thatcher, Michael Heseltine, John Major, William Hague, Boris Johnson and David Cameron.